Cortical Reorganization Following Psychoeducational Counselling and Residual Inhibition Therapy (RIT) in Individuals with Tinnitus - Vasudevan, Harini; Palaniswamy, Hari Prakash; Balakrishnan, Ramaswamy; Rajashekhar, Bellur (International Archives of Otorhinolaryngology, 2022)
Introduction Psychoeducational counselling and residual inhibition therapy (RIT) are traditional approaches used in many clinics to manage tinnitus. However, neurophysiological studies to evaluate posttreatment perceptual and functional cortical changes in humans are scarce.Objectives The present study aims to explore whether cortical auditory-evoked potentials (CAEPs; N1 and P3) reflect the effect of modified RIT and psychoeducational counselling, and whether there is a correlation between the behavioral and electrophysiological measures.Methods Ten participants with continuous and bothersome tinnitus underwent a session of psychoeducational counselling and modified RIT. Perceptual measures and CAEPs were recorded pre- and posttreatment. Further, the posttreatment measures were compared with age and gender-matched historical control groups.Results Subjectively, 80% of the participants reported a reduction in the loudness of their tinnitus. Objectively, there was a significant reduction in the posttreatment amplitude of N1 and P3, with no alterations in latency. There was no correlation between the perceived difference in tinnitus loudness and the difference in P3 amplitude (at Pz).Conclusion The perceptual and functional (as evidenced by sensory, N1, and cognitive, P3 reduction) changes after a single session of RIT and psychoeducational counselling are suggestive of plastic changes at the cortical level. The current study serves as preliminary evidence that event-related potentials (ERPs) can be used to quantify the physiological changes that occur after the intervention for tinnitus.
Keywords: residual inhibition therapy; tinnitus; psychoeducational counselling; treatment; cortical reorganization